The impact of agroforestry and other landuses on soil functional capacity - Adolfsson, Lena (SLU/Dept. of Ecology, 2008)
Deforestation, agricultural cultivation and overuse of land resources can lead to decreasing functional capacity of soil microorganisms, e.g. decreasing decomposition and mineralisation capacity and rate. Agroforestry systems have long been considered to have positive effect on soil conditions and there is a need to investigate if the functional capacity of the soil can be recovered by these practices to reverse land degradation in the tropics. The objective of this study was to compare the functional capacity and diversity of soils under different land use, measured as substrate utilization potential of the soil bacteria community. Samples along an intensification gradient from undisturbed forest, forest plantations, agroforestry fields, agricultural fields and the most disturbed eroded soil were taken from farms on the slopes of Mount Elgon in the Rift Valley province of western Kenya. The microbial substrate utilization was studied by using Biolog EcoPlatesTM and chemical and biological soil properties including pH, extractable P, total N, organic C, nitrates and microbial biomass C and N were determined.